2018
DOI: 10.1111/nyas.13623
|View full text |Cite
|
Sign up to set email alerts
|

Is refreshing in working memory impaired in older age? Evidence from the retro‐cue paradigm

Abstract: Impairments in refreshing have been suggested as one source of working memory (WM) deficits in older age. Retro-cues provide an important method of investigating this question: a retro-cue guides attention to one WM item, thereby arguably refreshing it and increasing its accessibility compared with a no-cue baseline. In contrast to the refreshing deficit hypothesis, intact retro-cue benefits have been found in older adults. Refreshing, however, is assumed to boost not one but several WM representations when se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 26 publications
(51 citation statements)
references
References 62 publications
7
30
0
Order By: Relevance
“…Moreover, including a perceptual matching task to ensure that younger and older adults did not differ in memory precision due to for instance greater motor noise in older adults may have been informative. However, Loaiza and Souza (2018) found that while there was an age difference in perceptual matching, it was much smaller than that observed in the WM task, suggesting that it did not fully account for the age differences in WM precision memory (see also, Souza, 2016;Loaiza & Souza, 2019). Also, age-related perceptual and/or motor differences are unlikely to vary between our experimental conditions.…”
Section: Limitationsmentioning
confidence: 67%
“…Moreover, including a perceptual matching task to ensure that younger and older adults did not differ in memory precision due to for instance greater motor noise in older adults may have been informative. However, Loaiza and Souza (2018) found that while there was an age difference in perceptual matching, it was much smaller than that observed in the WM task, suggesting that it did not fully account for the age differences in WM precision memory (see also, Souza, 2016;Loaiza & Souza, 2019). Also, age-related perceptual and/or motor differences are unlikely to vary between our experimental conditions.…”
Section: Limitationsmentioning
confidence: 67%
“…Results from retrocue paradigms, conversely, are akin to the use of attention to ignore an irrelevant content maintained in visual WM [55]. Although some initial studies pointed to age-deficits in using retrocues [56,57], subsequent studies have consistently obtained retrocue benefits of similar magnitude between younger and older adults [50,[58][59][60][61]. Together with the present findings, more and more behavioral evidence indicates that the source of the robust age-related decline observed in visual WM is unlikely to be explained by deficits in inhibiting irrelevant information.…”
Section: Aging Deficits In the Control Of Attention?mentioning
confidence: 99%
“…There is some evidence to suggest that the refreshing of memory representations is less effective in older adults (e.g. Fanuel, Plancher, Monsaingeon, Tillmann, & Portrat, 2018;Loaiza & McCabe, 2013; although see Loaiza & Souza, 2017;Souza, 2016 for conflicting evidence from a cued refreshing paradigm). That being said, by adjusting task demand for each individual to a common single task accuracy level, it may be argued that age-differences in prioritization cost will not appear.…”
Section: Deriving Predictions From Multiple Component Time-based Resmentioning
confidence: 99%